Exosomal microRNA signatures in youth at clinical high risk for bipolar disorder - Meng, Xinyu; Zhang, Shengmin; Xu, Yingzhen; Ma, Zaohui; Zhou, Shuzhe; Ma, Yantao; Ma, Hong; Yu, Xin; Guan, Lili (Frontiers in Psychiatry, 2025)
IntroductionIndividuals at clinical high risk for bipolar disorder (CHR-BD) experienced insufficient recognition. Little is known regarding the association between exosome microRNA (miRNA) profile and bipolar disorder (BD) risk.Materials and methodsTwenty youth at CHR-BD, 21 patients with BD, and 24 healthy controls were recruited in this study. Exosomal small RNA sequencing was undertaken in the plasma sample of the participants. Using machine-learning algorithms, target miRNAs were selected from differentially expressed candidates. Predictive models were built and tested on validation set.ResultsThe study identified two miRNAs that showed significantly differential expression between the CHR-BD group and the HC group: hsa-miR-184 (log2FC = 4.22, P = 1.49E-04) and hsa-miR-196a-5p (log2FC = 4.75, P = 3.56E-04). Random forest (RF) and eXtreme Gradient XGBoost jointly selected two overlapping miRNAs: hsa-miR-1908-3p and hsa-miR-412-5p. XGBoost outperformed the RF model with higher AUCs (BD group: 0.71 vs 0.71, CHR-BD group: 0.74 vs 0.72, HC group: 0.60 vs 0.57).ConclusionThe study identified four target miRNAs involved in neuroimmunity and neuronal plasticity, supported by literature linking these miRNAs to neuropsychiatric diseases, suggesting their potential as biomarkers for early BD. Future research should integrate additional biomarkers for improved discriminative performance.